The introduction of Observation-Based Physics into the WAM Wave Model and Wave-Coupled Interactions - Kousal, Joshua S. (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2022)
Ocean surface waves are an unparalleled ocean phenomenon, wreaking havoc on ocean-going vessels and spreading their tendrils into effects on many aspects of weather and climate. To understand and predict these waves, the best tool available is the third-generation spectral wave model. These models predict the growth, decay, and transformation of wind-generated waves. The modern wave physics package for such models is the observation-based approach developed by A. V. Babanin, I. R. Young, M. A. Donelan, M. L. Banner and W. E. Rogers (hereafter BYDBR). Its source functions were measured and therefore are not subject to tuning (within confidence limits of the measurements). Furthermore, the observations revealed and/or quantified physical phenomena missing or neglected in other source-term packages for spectral wave models such as non-linear airflow separation (hence relative reduction of wind input at strong winds), steepness-dependent wave growth (making the wind input a weakly non-linear function of the wave spectrum), negative wind input under adverse winds, two-part wave dissipation consisting of a local in wavenumber space term and a cumulative term (which is an integral of the spectrum), a wave breaking threshold below which no breaking occurs, and swell decay due to interaction with and production of oceanic turbulence. This observation-based physics is available in two of the three dominant third- generation spectral wave models, WAVEWATCH-III and SWAN, but not yet WAM, the introduction of which (coding, testing and validation for both the ECMWF- and Hereon-managed versions of WAM) is a key outcome of this thesis, and enables its use by the remaining third of the research and practical oceanographic community. This observation-based physics is primarily concerned with the open ocean however, and neglects regions which are dominated by different physical processes, such as the polar regions. These regions are amongst those changing most rapidly in response to climate change, and contribute the large ...